2020
DOI: 10.1029/2020gl090152
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between Shallow Cumulus Cloud Field Properties and Surface Solar Irradiance

Abstract: Shallow cumulus clouds exhibit highly three-dimensional (3-D) spatial structure leading to complex variability in the surface solar irradiance (SSI) beneath. This variability is captured by the typically bimodal shape of the SSI probability density function (PDF). Using large eddy simulation to generate well-resolved cloud fields and Monte Carlo 3-D radiative transfer to reproduce realistic associated SSI PDFs, we seek direct relationships between the cloud field properties and the SSI PDF shape. Applying both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 28 publications
5
30
0
Order By: Relevance
“…These results agree with previous studies, for instance similar parameters were found to explain the PDF of surface solar irradiance under 3D cumulus clouds using machine learning in Gristey et al. (2020a). Note however that since the extent to which the different parameters were perturbed is not uniform, their relative importance is not thoroughly quantified here.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with previous studies, for instance similar parameters were found to explain the PDF of surface solar irradiance under 3D cumulus clouds using machine learning in Gristey et al. (2020a). Note however that since the extent to which the different parameters were perturbed is not uniform, their relative importance is not thoroughly quantified here.…”
Section: Resultssupporting
confidence: 93%
“…Surface albedo and overlap parameters have small impact: doubling the surface albedo only slightly increases the total downward flux at the surface, while changing the overlap parameter both changes radiation and cloud cover and hence preserves the average DTR computed over a given cloud cover sub-interval. These results agree with previous studies, for instance similar parameters were found to explain the PDF of surface solar irradiance under 3D cumulus clouds using machine learning in Gristey et al (2020a). Note however that since the extent to which the different parameters were perturbed is not uniform, their relative importance is not thoroughly quantified here.…”
Section: Resultssupporting
confidence: 91%
“…Surface albedo and overlap parameters have small impact: doubling the surface albedo only slightly increases the total downward flux at the surface, while changing the overlap parameter both changes radiation and cloud cover and hence preserves the average DTR computed over a given cloud cover sub-interval. These results agree with previous studies, for instance similar parameters were found to explain the PDF of surface solar irradiance under 3D cumulus clouds using machine learning in Gristey et al (2020a). Note however that since the extent to which the different parameters were perturbed is not uniform, their relative importance was not thoroughly quantified here.…”
Section: Resultssupporting
confidence: 91%
“…The RF is used to predict the perturbed SSI PDF shape in the presence of aerosol. This PDF shape is quantified in a similar manner as described in Gristey et al (2020a) so the reader is referred there for full details. A brief summary is provided again here for completeness.…”
Section: Machine Learning To Map Between Aerosol and Cloud Field Prop...mentioning
confidence: 99%
“…where 𝐴𝐴 𝜽𝜽 is the location parameter (a horizontal shift of the distribution), 𝐴𝐴 𝒔𝒔 is the shape parameter (the standard deviation of the log of the distribution), and 𝐴𝐴 𝒎𝒎 is the scale parameter (the median of the distribution). The only difference compared with Gristey et al (2020a) is that here we fit the mirror image of the large SSI mode in the presence of aerosol. This is because the presence of aerosol causes the tail of the large SSI mode to extend in the opposite direction (see Section 3.1 and Figure 4b).…”
Section: Machine Learning To Map Between Aerosol and Cloud Field Prop...mentioning
confidence: 99%